Multidimensional Balanced Efficiency Decision Model - Antonella Petrillo; Fabio De Felice (Journal of Technology Management & Innovation, 2015)
In this paper a multicriteria methodological approach, based on Balanced Scorecard (BSC) and Analytic Network Process (ANP), is proposed to evaluate competitiveness performance in luxury sector. A set of specific key performance indicators (KPIs) have been proposed. The contribution of our paper is to present the integration of two methodologies, BSC – a multiple perspective framework for performance assessment – and ANP – a decision-making tool to prioritize multiple performance perspectives and indicators and to generate a unified metric that incorporates diversified issues for conducting supply chain improvements. The BSC/ANP model is used to prioritize all performances within a luxury industry. A real case study is presented.